Kaji Eksperimental Getaran Roda Gila pada Sepeda Statis - Amir Zaki Mubarak; Reza P. Munirwan; Asbar Razali (Jurnal Teknik Mesin Unsyiah, 2014)
The use of flywheel as an energy storing device has been introduced in various mechanical systems. In this paper is discussed the use of it on a stationary bicycle. The flywheel technology is utilised on the bicycle to provide as well as distribute the load in cycling. The focus of the research is the affectivity of the flywheel usage considered from the vibration occurred. In this research, a new model of stationary bicycle is designed to have a reliable and comfortable stationary bicycle. Thus, the vibration caused by the flywheel is one of the concern that an experimental study has been conducted. Based on the experimental test it concluded that the vibration occurred is moderate that the design of the bicycle is acceptable for use.